Functional Consequences of the Oligomeric Assembly of Proteorhodopsin. Issue 6 (27th March 2015) - Hussain, Sunyia; Kinnebrew, Maia; Schonenbach, Nicole S.; Aye, Emily; Han, Songi
Abstract: The plasma membrane is the crucial interface between the cell and its exterior, packed with embedded proteins experiencing simultaneous protein–protein and protein–membrane interactions. A prominent example of cell membrane complexity is the assembly of transmembrane proteins into oligomeric structures, with potential functional consequences that are not well understood. From the study of proteorhodopsin (PR), a prototypical seven-transmembrane light-driven bacterial proton pump, we find evidence that the inter-protein interaction modulated by self-association yields functional changes observable from the protein interior. We also demonstrate that the oligomer is likely a physiologically relevant form of PR, as crosslinking of recombinantly expressed PR reveals an oligomeric population within the Escherichia coli membrane (putatively hexameric). Upon chromatographic isolation of oligomeric and monomeric PR in surfactant micelles, the oligomer exhibits distinctly different optical absorption properties from monomeric PR, as reflected in a prominent decrease in the p K a of the primary proton acceptor residue (D97) and slowing of the light-driven conformational change. These functional effects are predominantly determined by specific PR–PR contacts over nonspecific surfactant interactions. Interestingly, varying the surfactant type alters the population of oligomeric states and the proximity of proteins within an oligomer, as determined by sparse electron paramagnetic resonance distance measurements. Nevertheless, the dynamic surfactant environment retains the key function-tuning property exerted by oligomeric contacts. A potentially general design principle for transmembrane protein function emerges from this work, one that hinges on specific oligomeric contacts that can be modulated by protein expression or membrane composition. Graphical abstract: Highlights: Functional implications of transmembrane protein oligomers are not well understood. Crosslinking establishes that PR oligomers are present in the bacterial membrane. Oligomers and monomers of PR are isolated in surfactant micelles. Specific oligomeric interactions tune measurable light-driven PR activity. Oligomerization is established as a key determinant of PR function.